Faktor Penyebab Munculnya Hubungan Prasangka dan Frustrasi dengan Perilaku Agresif Remaja - Selly Anggraini Inshani; Fenty Zahara Nasution (Jurnal Rumpun Ilmu Kesehatan, 2023)
Teenagers experience problems due to not achieving needs, for example they want to be recognized as adults but their behavior still looks like children. If adolescents fail to develop a sense of identity, then adolescents will lose their way and have a bad impact on their development. Frustration can lead the individual to aggressive behavior because frustration for the individual is an unpleasant situation and the individual wants to overcome or avoid it in various ways, notonly in an aggressive way. The purpose of the study was to determine the factors causing the emergence of prejudiced and frustrated relationships with aggressive behavior of adolescents. This study utilizes the study literatur review. Based on the results of the study, it is stated that the causes of adolescents to take aggressive actions are due to: (1) Internal Factors (a) Weak Self-Control can be difficult to control emotions, therefore a person who has weak self-control will easily act aggressively on anyone. (b) The occurrence of frustration Because a bad event causes the subject to become frustrated with his current life. (c) Gender differences.